Associations between air pollutant exposure and renal function: A prospective study of older adults without chronic kidney disease. (15th May 2021) - Li, Ang; Mei, Yayuan; Zhao, Meiduo; Xu, Jing; Li, Runkui; Zhao, Jiaxin; Zhou, Quan; Ge, Xiaoyu; Xu, Qun
Abstract: We used real-world exposure scenarios to evaluate the effect of six ambient air pollutant (PM2.5, PM10, NO2, SO2, CO, and O3 ) exposure on renal function among older adults without chronic kidney disease (CKD). We recruited 169 older adults without CKD in Beijing, China, for a longitudinal study from 2016 to 2018. The Modification of Diet in Renal Disease (MDRD) and the Chronic Kidney Disease Epidemiology Collaboration (EPI) equations were employed to derive the estimated glomerular filtration rate (eGFR). A linear mixed-effects model with random intercepts for participants was employed to determine the effects of air pollutants on renal function evaluated on the basis of eGFR and urinary albumin/creatinine ratio at different exposure windows (1-, 2-, 3-, 5-, 7-, 14-, 28-, 45-, and 60-days moving averages). An interquartile range (IQR) increase in NO2 for was associated with significant decreases of in eGFR (MDRD equation) [percentage changes: −4.49 (95% confidence interval: −8.44, −0.37), −5.51 (−10.43, −0.33), −2.26 (−4.38, −0.08), −3.71 (−6.67, −0.65), −5.44 (−9.58, −1.11), −5.50 (−10.24, −0.51), −6.15 (−10.73, −1.33), and −6.34 (−11.17, −1.25) for 1-, 2-, 5-, 7-, 14-, 28-, 45-, and 60-days moving averages, respectively] and in eGFR (EPI equation) [percentage changes: −5.04 (−7.09, −2.94), −6.25 (−8.81, −3.62), −5.16 (−7.34, −2.92), −5.10 (−7.85, −2.28), −5.83 (−8.23, −3.36), −6.04 (−8.55, −3.47) for 1-, 2-, 14-, 28-, 45-, and 60-days moving averages, respectively]. In two-pollutant model, only the association of NO2 exposure with eGFR remained robust after adjustment for any other pollutant. This association was stronger for individuals with hypertension for the EPI equation or BMI <25 kg/m 2 for the MDRD equation at lags 1 and 1–2. Our findings suggest that NO2 exposure is associated with eGFR reduction among older adults without CKD for short (1-, 2-days) and medium (14-, 28-, 45-, 60-days) term exposure periods; thus, NO2 exposure may contribute to renal impairment. Graphical abstract: Image 1 Highlights: Association between air pollution exposure and renal function were assessed. We studied a vulnerable population (older, non-chronic kidney disease adults). Short- and medium-term NO2 exposure is associated with eGFR reduction. NO2 influenced renal function impairment depending on comorbidity status. These results should inform policies to further control the source of NO2 . Abstract : NO2 exposure is associated with eGFR reduction among older adults without CKD. The effect on renal function depends on comorbidity status.